2023
DOI: 10.1088/1755-1315/1165/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Moonlight and Rainfall Influence Efficacy of Sex Pheromones in Controlling Spodoptera exigua (Lepidoptera: Noctuidae) on Shallot

Abstract: Shallot (Allium ascalonicum L.) is one of the horticultural commodities that have high economic value in Indonesia. The caterpillar, Spodoptera exigua Hübner (Lepidoptera: Noctuidae), is an important pest of shallot crops which decreases both production and yield quality. Farmers commonly spray pesticides to control S. exigua. This can cause negative impacts on the environment and farmers’ health. Therefore, environmentally friendly control measures need to be implemented. Use of sex pheromone traps can be an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…During the off-season, when the rainfall is high, the number of S. exigua captured decreases, and when the rainfall is low, the number increases again (Figure 2). This result aligns with Hidayah et al (2023), who found that the number of male S. exigua captured tends to decrease on rainy days. Meanwhile, in the onseason conditions, the number of S. exigua captured is also high when the rainfall is high, and when the rainfall is low, the number of captured individuals is also low.…”
Section: Resultssupporting
confidence: 91%
“…During the off-season, when the rainfall is high, the number of S. exigua captured decreases, and when the rainfall is low, the number increases again (Figure 2). This result aligns with Hidayah et al (2023), who found that the number of male S. exigua captured tends to decrease on rainy days. Meanwhile, in the onseason conditions, the number of S. exigua captured is also high when the rainfall is high, and when the rainfall is low, the number of captured individuals is also low.…”
Section: Resultssupporting
confidence: 91%